“Mi laboratorio de artesanía”: un proyecto para la valoración de los beneficios de la ciencia y la tecnología, articulado por el diseño - Alfaro Matamoros, Elena (2024)
My Artesanal Laboratory is a project funded by the Explora Program of the National Commission for Scientific and Technological Research (CONICYT) ―currently Public Science― in its line of Valuing Science and Technology; executed by the Artesanals Program of the School of Design of the Pontifical Catholic University of Chile. Its objective was to develop a multipurpose kit that allows children between 6 and 10 years old and their families, through observation, questions and experimentation, to learn about traditional artisanal expressions from indigenous peoples present in the national territory, identifying them as technological solutions that respond to scientific principles applied empirically by human beings since ancient times. This is an interdisciplinary project that is articulated through design, and in which traditional oral knowledge and artesanal artifacts are positioned as the backbone of a research applied to education, in which designers, teachers, artesanals women, scientists, engineers and journalists, among other professionals, participated. As a result of the project, 300 multipurpose kits of two types were produced, one dedicated to Aymara Science and Technology and the artesanal of Textiles, and the other to Lafkenche Mapuche Science with a focus on basketry in vegetable fibers, which were distributed free of charge in 8 regions of the territory. In addition, a web page was generated with the content released for use and a series of face-to-face workshops began to be held after the pandemic. The project is supported by the Fundación Artesanías de Chile as a partner institution and also by the Agricultural Development Institute, INDAP.